2000
DOI: 10.1039/a909041j
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic diaryliodonium ions: old mysteries solved and new applications envisaged

Abstract: For a long time the unusually poor reactivity of cyclic diaryliodonium ions toward nucleophiles remained a mystery. Only very recently has a solution to this puzzle been found, shedding light on the mechanism of aromatic nucleophilic substitution reactions of iodonium salts. This article provides an overview of the most important current advances in the field, both theoretical and practical.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
93
0
4

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 221 publications
(102 citation statements)
references
References 21 publications
3
93
0
4
Order By: Relevance
“…[13,14,60] Cyclic diaryliodonium salts are generally easier to form than the corresponding acyclic structures. [61] Thus, it is not surprising that one of the first one-pot procedures involved cyclic structures. In 1956, Sandin and co-workers reported that treatment of 2-iodobiphenyl and similar compounds with peracetic acid, followed by addition of sulfuric acid brought about ring closure (Scheme 8 b).…”
Section: One-pot Synthesesmentioning
confidence: 99%
“…[13,14,60] Cyclic diaryliodonium salts are generally easier to form than the corresponding acyclic structures. [61] Thus, it is not surprising that one of the first one-pot procedures involved cyclic structures. In 1956, Sandin and co-workers reported that treatment of 2-iodobiphenyl and similar compounds with peracetic acid, followed by addition of sulfuric acid brought about ring closure (Scheme 8 b).…”
Section: One-pot Synthesesmentioning
confidence: 99%
“…When (diacetoxyiodo)benzene and diphenyl phosphate reached to two equivalents, the yield was increased to 43% (entry 6); while two equivalents of acetophenone were used to reacted with one equivalent of (diacetoxyiodo)benzene and diphenyl phosphate, the reaction got the higher yield of 48% (entry 7). We found that the product of α-phosphoryloxyl acetophenone was partly decomposed in separation and the yield was decreased much, then we used 1 H NMR technique to show the true yield and after 24 h the reaction reached the highest yield of 80% (entries [8][9][10][11][12][13].…”
Section: Resultsmentioning
confidence: 99%
“…23 Also, alkylideneoxazoline has been known to be isomerized to oxazole by acid. 24 Finally, the substitution of phenyliodonium group of Int-E by AcOH and/or the reductive elimination of PhI 25,26 would give the target oxazoles 2. Accordingly, the introduction of deuterium in the formation of d1-2a from 1a (Scheme 5) would depend on (i) the deuteration of Int-G by AcOD or (ii) the addition of AcOD to iodonium ylide Int-D, both steps of which would be involved in the case of d2-2a.…”
Section: Scheme 5 H/d Exchange Experimentsmentioning
confidence: 99%